2008
DOI: 10.1007/s00421-008-0750-6
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral arm strength training improves contralateral peak force and rate of force development

Abstract: Neural adaptation following maximal strength training improves the ability to rapidly develop force. Unilateral strength training also leads to contralateral strength improvement, due to cross-over effects. However, adaptations in the rate of force development and peak force in the contralateral untrained arm after one-arm training have not been determined. Therefore, we aimed to detect contralateral effects of unilateral maximal strength training on rate of force development and peak force. Ten adult females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 39 publications
1
43
1
6
Order By: Relevance
“…The results of effective programs are usually observed as increased one repetition maximum (1RM) or improved ability to develop force and power. While muscle hypertrophy is associated with increased cross-section of the myocyte and whole-muscle 6,7 , neural adaptation is not 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The results of effective programs are usually observed as increased one repetition maximum (1RM) or improved ability to develop force and power. While muscle hypertrophy is associated with increased cross-section of the myocyte and whole-muscle 6,7 , neural adaptation is not 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have investigated cross training following strength training. For example, Adamson et al 10 reported that unilateral arm strength training improves contralateral peak force and rate of force development .Accordingly, cross-training effect has been observed in different muscles groups after different mode of exercise training and at different levels of task complexity 9,11 . It has been reported that crosstraining process is primarily caused by adaptations in the central nervous system CNS) for the untrained limb following exercise training 12,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Com isso, o tempo reduzido de contração durante movimentos rápidos do membro, pode não permitir que se atinja a força máxima muscular. Neste caso, a melhor análise a ser realizada é a determinação do aumento da força, a partir do início da contração, através da TDF ADAMSON et al, 2008;THORLUND et al, 2008), TDT (CONNELLY;VANDERVOORT, 2000) e taxa de desenvolvimento de velocidade (TDV) (BROWN; WHITEHURST, 2003;FINDLEY et al, 2006;MILLER et al, 2006). Figura 1.4.…”
Section: Efeitos Do Exercício Excêntrico Nas Propriedades Mecânicas Dunclassified
“…Com o mesmo propósito, a taxa de aumento de força em contrações dinâmicas tem sido analisada no joelho (THORLUND et al, 2008), tornozelo (CONNELLY; VANDERVOORT et al, 2000) e ombro (ADAMSON et al, 2008). O pico TDT é observado próximo de 90ms em extensão do joelho sem carga (ANDERSEN et al, 2005), sendo que a melhor correlação entre a taxa isométrica e dinâmica de aumento da força ocorre neste momento (THORLUND et al, 2008).…”
Section: Análise Estatísticaunclassified
See 1 more Smart Citation